ANALYSIS OF EXTRINSIC ELEMENTS IN NADINE LABAKI'S CAFERNAUM FILM: Analisis Unsur Ekstrinsik Dalam Film Cafernaum Karya Nadine Labaki - Bintang Rosada (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2023)
Abstract: Film is a literary work (prose) that contains the life story of a person or various characters packaged in imaginative works, so that it attracts the interest of many readers, where in the film itself there are various elements that can be used as life lessons in real life. This research includes descriptive qualitative research with the type of literature research (library). The data was taken from several journals, books, e-books, newspapers and others. This data set was processed using triangulation, where the data was sorted and adjusted to suit this research. The film Capernaum by Nadine Labaki is one of the films on the realization of children's rights which is part of a literary work, where the film contains extrinsic elements that show the life of the author (Nadine Labaki) which includes: the author's background, society's background, and values. contained in the film. background regarding the film's author, Nadine Labaki, a film director who lives in a heterogeneous Lebanese society, asked him to voice the human rights of children, by casting non-professional actors to make the film feel more alive and real. The civil war resulting from friction between groups who wanted to maintain their existence caused long chaos in Lebanon which sacrificed the human rights of children who lived in suffering, injustice and oppression. Keywords: Extrinsic Elements, Capernaum, Nadine Labaki مستخلص البحث: الفيلم هو عمل أدبي (نثر) يحتوي على قصة حياة شخص أو شخصيات مختلفة معبأة في أعمال خيالية، بحيث يجذب اهتمام الكثير من القراء، حيث يوجد في الفيلم نفسها عناصر مختلفة يمكن الاستفادة منها كدروس في الحياة الحقيقية. يشتمل هذا البحث على بحث وصفي نوعي الأدبي (المكتبة). تم أخذ البيانات من المجلات والكتب الإلكترونية والصحف وغيرها. تمت معالجة مجموعة البيانات هذه باستخدام التثليث، حيث تم فرز البيانات وتعديلها لتناسب هذا البحث. يعد فيلم كفرناحوم لنادين لبكي أحد الأفلام التي تناولت إعمال حقوق الطفل وهو جزء من عمل أدبي، حيث يحتوي الفيلم على عناصر خارجية تظهر حياة المؤلفة (نادين لبكي) والتي تشمل خلفية المؤلف والمجتمع والقيم التي يتضمنها الفيلم. الكلمات المفتاحية: العناصر الخارجية، كفرناحوم، نادين لبكي.